Ecofriendly Management of Two Spotted Spider Mites on Tomato (Solanum lycopersicum) (Mill) in Eastern Ethiopia - Dabalo, Belachew (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was initiated with the objective to evaluate the efficacy of tobacco leaf extract and potentiality of intercropping on TSSM in Eastern Ethiopia. The tomato, tomato + cabbage, tomato + common bean, tomato + onion, tomato + tobacco leaf extract and tomato + karate 5% EC were the treatments used for the trial. The overall result indicated that intercropping and tobacco leaf extract significantly reduced the population of these mite pests compared to sole tomato. The minimum population with infestation was recorded on karate (14.65, 0.79) followed by tomato – tobacco leaf extract (16.50, 0.92) and tomato onion (36.53, 1.74) from intercropping while control was the most in recording maximum population with maximum infestation (94.10, 2.88 respectively). The most population reduction with infestation was observed on tobacco leaf extract compared to untreated plot followed by tomato-onion intercropping. The highest yield (50.73tha-1) was recorded on the tomato-onion intercrops followed by karate 5%EC (43.96tha-1) and tobacco extract (43.65tha-1) while the lowest yield was recorded on head cabbage intercrops (30.10tha-1). The maximum net benefit was obtained from tomato-onion intercrops (688653.45 ETB) whereas the lowest net benefit was recorded on common bean (354176.60 ETB) intercrops. Therefore, tomato onion intercrops and tobacco leaf extract could be considered as the first options in boosting tomato production as an alternative to karate 5%EC and expected as common integrated management of TSSM on tomato.